2018
DOI: 10.1039/c8fd00006a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoengineering ABO3active sites from low-energy routes (TX100-stabilised water-in-oil microemulsions, surface segregation and surface complexation on colloidal AlOOH/sol–gel Al2O3surfaces) for pollution control catalysis

Abstract: It is shown that water-in-oil microemulsions (m/e or mE) can produce BaCeO 3 (BCO) and LaCoO 3 (LCO) precursors. The nanoparticles (NPs) adsorb on AlOOH sols, in much the same way as Turkevich previously immobilised platinum group metal sols. BCO is active in CO and propane oxidation and NO removal under stoichiometric exhaust conditions, but LCO is a better oxidation catalyst. Activity was also seen when Ba,Ce and La,Co are inserted into/segregate at the surface of AlOOH/Al 2 O 3 . However, there is only form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…A rise in temperature promotes the conversion of the positive ions of protein into chalcone and consequently leads to protein degradation . [4,11,22] When the protein solution was under 60°C, the protein retention rate was only 13% after 15 d (p < .01). According to Figure 5B, Proteins exhibited a significantly increased retention rate of 63.5% at 60°C for 15 d after microemulsion embedding (p < .01).…”
Section: Temperature Stability Of Desmodium Intortum Protein Microemulsionmentioning
confidence: 99%
See 2 more Smart Citations
“…A rise in temperature promotes the conversion of the positive ions of protein into chalcone and consequently leads to protein degradation . [4,11,22] When the protein solution was under 60°C, the protein retention rate was only 13% after 15 d (p < .01). According to Figure 5B, Proteins exhibited a significantly increased retention rate of 63.5% at 60°C for 15 d after microemulsion embedding (p < .01).…”
Section: Temperature Stability Of Desmodium Intortum Protein Microemulsionmentioning
confidence: 99%
“…Once the proportion is determined, a similar microemulsion can be produced. [11] The commonly used food-grade surfactants are soybean lecithin, Tween, span, and sucrose fatty acid ester . [12][13][14] Some studies have shown that the emulsifying effect on the stability of microemulsion of combined surfactant is better than that of a single surfactant, the stability of microemulsion is better.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation